Firearm presence and storage practices in North Carolina homes. Issue 7 (3rd October 2017) - Imai, Satomi; Rafferty, Ann; Jones, Katherine; Mansfield, Chris; Proescholdbell, Scott
ABSTRACT: Firearms injuries are a leading cause of injury and death in North Carolina, including suicide, homicide, intentional assault, and unintentional injuries. Research has demonstrated that the presence of a firearm in a household increases the risk for homicide and suicide. This study examined two firearms-related risk factors, the presence of a firearm in the household and risky storage practices (loaded and unlocked), using the 2011 North Carolina Behavioral Risk Factor Surveillance System (BRFSS). We hypothesized that among household firearm owners, those who keep unlocked loaded firearms would be varied by demographic variables and also by tendencies for more risk-taking behaviors such as smoking and drinking. Results showed that those who were more likely to keep firearms in or around the home were male, older age, White race, married, with some post high school education, and with higher income. There were no differences by region, age, race, education, or income among those who kept firearms loaded and unlocked. Risky storage practices were related to social conditions such as marital status and number of adults and children in the household. The presence of firearms was lower among those who lived alone; however, among those with a firearm in the household, 42% of single adult households keep a loaded and/or unlocked firearm in the house, and up to 30% of households with children do as well. Behavioral risk factors such as smoking, binge drinking, and not using a seatbelt when driving a car were also related to firearms possession and storage conditions.